Consumo colaborativo: investigando o consumo de caronas mediadas por tecnologias sob a ótica da Consumer Culture Theory (CCT) - Rosa, Ana Claudia da (2023)
Inserted in the context of collaborative consumption, collaborative rides measured by technologies were chosen as the locus of this research (MACÊDO et al., 2021). The research was anchored in the theoretical lens of the CCT, seeking to consider, in addition to consumers' perceptions, their context and embrace the complexity of the present in the practice of collaborative consumption of ridesharing (ARNOULD; THOMPSON, 2005; MOURA, 2018; PINTO et al. , 2015). From the research gaps and justifications, the objectives and questions that guided the development of this thesis were elaborated. The general objective of this research was: To analyze the collaborative consumption of carpooling mediated by technologies from the theoretical lens of the Consumer Culture Theory (CCT). For this, a qualitative research was carried out, through 23 in-depth interviews with consumers of collaborative rides. As an analysis technique, content analysis was postulated (BARDIN, 2015; RESENDE, 2018). The general objective was achieved through reflections on this consumption from the personal and sociocultural aspects. From the initial categories of the research, the intermediate categories were built, and later, the final ones. Among the results of this thesis, an important theoretical contribution was the investigation of consumption, encompassing elements present in collaborative consumption from the theoretical lens of CCT. Regarding practical contributions, this research brings relevant findings to the most diverse stakeholders: providers and developers of collaborative applications, drivers, and other consumers. Another contribution refers to identifying the presence of the pandemic in consumer behavior. Finally, as socio-environmental contributions, it was noticed that, despite not being the main reason for choosing consumers, some are aware of the socio-environmental benefits present in the collaborative consumption of rides.